Strategi Guru Akidah Akhlak dalam Pembentukan Kedisiplinan dan Kesantunan Berbahasa Siswa di MI Sailul Ulum Pagotan Madiun - Hidayatul Maghfiroh; Jauhan Budiwan; Moh. Masduki (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
This study aims to analyze the strategies employed by Akidah Akhlak teachers in fostering students’ discipline and language courtesy at MI Sailul Ulum Pagotan Madiun. The research is grounded in the belief that Akidah Akhlak education plays a vital role in shaping students’ moral character, particularly in building disciplined attitudes and polite communication as reflections of Islamic values. Using a qualitative descriptive approach, the study was conducted at MI Sailul Ulum Pagotan Madiun with research subjects consisting of Akidah Akhlak teachers, the head of the madrasa, homeroom teachers, and students. Data were collected through interviews, observation, and documentation, and analyzed using John W. Creswell’s interactive model, which includes data reduction, coding and categorization, data display, theme identification, and conclusion drawing. The findings reveal four main strategies implemented by Akidah Akhlak teachers: exemplary behavior (uswah hasanah), habituation, advice and motivation, and supervision with persuasive rule enforcement. Teachers act as primary role models of discipline and politeness, reinforce these values through daily religious practices such as morning prayers, Qur’an recitation, and Dhuha congregational prayer, and use humanistic approaches to encourage students’ self-awareness. The success of these strategies is supported by a religious school environment, strong leadership, and teacher collaboration, while inhibiting factors include family background differences, social media influence, and diverse student characters. Overall, the study concludes that consistent modeling and continuous moral guidance are essential to sustain students’ disciplined and courteous behavior.